Gestational and childhood urinary triclosan concentrations and academic achievement among 8-year-old children. - Jackson-Browne, Medina S. (Neurotoxicology, 2020)
BACKGROUND: Early life exposure to triclosan, an antimicrobial chemical and suspected endocrine disruptor, may adversely affect neurodevelopment. No studies have examined gestational and early childhood exposure to triclosan and children’s academic achievement. METHODS: Using data from 193 mother-child pairs from the HOME Study, we quantified triclosan in maternal and child urine samples up to nine times between the second trimester of gestation (16-weeks) and age 8 years. At age 8 years, we administered the reading and math components of the Wide Range Achievement Test-4 (WRAT-4) to children. Using multiple informants models, we estimated covariate-adjusted associations of triclosan concentrations during each time period with WRAT-4 scores. We also tested whether associations differed by exposure period and child sex. RESULTS: There was evidence that timing of exposure modified the associations between triclosan and reading composite scores (triclosan-exposure period interaction p-value=0.20), but not math scores (interaction p-value=0.72). Each 10-fold increase in triclosan concentrations at delivery was associated with lower reading composite scores (β:−2.6; 95% CI:−5.0, −0.1). Additionally, we observed weaker and less precise inverse association of math scores with triclosan concentrations at delivery (β:−1.9; 95% CI:−4.6, 0.8) and at age 1 year (β:−2.0; 95% CI:−6.0, 2.1). There was not strong evidence that child sex modified the pattern of associations between repeated triclosan measures and WRAT-4 reading composite or math scores (sex-triclosan-exposure period interaction p-values>0.20). CONCLUSION: Urinary triclosan concentrations at delivery and at age 1 year, but not other times during gestation or childhood, were associated with lower reading composite and to a lesser extent math test scores at age 8 years in this cohort of U.S. children.